Addition of legumes in the Formulation of Supplementary Food Based on Palm Starch (Arenga Pinnata (Wurmb) Merr) - Aryani Kusumaningrum; Winiarti P Rahayu (Jurnal Teknologi dan Industri Pangan, 2007)
Food diversification is one of the governmental programs to reduce rice demand. Palm starch (Arenga Pinnata (Wurmb) Merr) has a good potency as carbohydrate source for supplementary food. Supplementary food from palm starch enriched with 4 legumes (red bean, green bean, soy bean, and paenut)as sourch of protein were formulated. This weaning food was made by wet mixing all substances, then cooked at temperatur 750C for 10 minutes. The dough was then dried using drum dryer and milled. The flour was fortified by vitamin premix (vitamin A, vitamin D, and vitamin C), mineral premix (Na, Zn, Fe, Ca, and I) and vanilla flavor (0,05; 0,10; 0,15; 0,20; and 0,25%) to improve their nutritional and sensory qualities. Result obtained from hedonic tes indicated that soy bean is the most suitable bean 0,05 percent of vanilla flavor gave the best formula. Supplementary food from sugar palm starch contained 170 kkal energy, 4 g protein, 33g carbohydrate and 3 g fat per serving (42 g). If the formula was consumed three times per day it will fulfill 60 percent of AKG (Angka Kecukupan Gizi(Nutritional Daily Requirement)) of the baby and child’s protein. The protein digest of such supplementary food from sugar palm starch was 86,29 percent of casein and comply this with SNI 01-7111.4 -2005 and codex (1976) standard. Key words : Palm starch, legumes, weaning food